IMPLEMENTATION OF ELECTRICAL INSTALLATION PROPS AT YAPIN KERTASEMAYA SENIOR HIGH SCHOOL - Fatwasauri, Icha; Haryanti, Tri; Wardika, Wardika; Arzaq, Lathoiful; Maulana, Damar; Safitri, Safitri (LPPM Univ. Ibn Khaldun Bogor, 2023)
Physics is one of the subjects that is a scourge for students majoring in Natural Sciences at Yapin Kertasemaya High School. Based on the results of the team's interview with the physics teacher, it was found that the students were weak in electricity. In overcoming this problem, a teaching tool is made to learn basic electricity. From the results of community service activities, it can be seen that students are very enthusiastic and easily understand the material provided using teaching aids.